1997
DOI: 10.1084/jem.186.11.1897
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Regulation of B Cell Antigen Receptor Signaling by CD19: Selective Requirement for PI3-Kinase Activation, Inositol-1,4,5-Trisphosphate Production and Ca2+ Mobilization

Abstract: Genetic ablation of the B cell surface glycoprotein CD19 severely impairs the humoral immune response. This requirement is thought to reflect a critical role of CD19 in signal transduction that occurs upon antigen C3dg coligation of antigen receptors with CD19 containing type 2 complement receptors (CR2). Here we show that CD19 plays a key accessory role in B cell antigen receptor signaling independent of CR2 coligation and define molecular circuitry by which this function is mediated. While CD19 is not requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 80 publications
8
119
1
Order By: Relevance
“…However, the role of PI3K in Ag receptor-stimulated primary T and B cells differs in at least three respects. First, acute calcium mobilization is blocked by PI3K inhibitors in B cells (26) but not in T cells (30). Second, up-regulation of the activation marker CD25 is blocked by LY294002 in B cells (our unpublished observations) but not in T cells (16).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the role of PI3K in Ag receptor-stimulated primary T and B cells differs in at least three respects. First, acute calcium mobilization is blocked by PI3K inhibitors in B cells (26) but not in T cells (30). Second, up-regulation of the activation marker CD25 is blocked by LY294002 in B cells (our unpublished observations) but not in T cells (16).…”
Section: Discussionmentioning
confidence: 98%
“…Pretreatment with PI3K inhibitors reduces BCR-dependent calcium mobilization (26) as well as phosphorylation of Akt and S6K1 (Fig. 3 and Refs.…”
Section: Discussionmentioning
confidence: 99%
“…This did not account for all of the inhibition observed with Lyn, suggesting that additional mechanisms contribute to Lyn-mediated down-regulation of Btk pathways. These may include inhibition by the cell surface receptor PIR-B, a pathway shown to involve both Btk and Lyn (75,76 The reduced TNP-Ficoll responses in both CD19 Ϫ/Ϫ Btk lo and p85␣ ϩ/Ϫ Btk lo mice supports a model in which CD19 amplifies Btk activation via PI3K (61,62). p85␣ was more penetrant than CD19, however.…”
Section: Discussionmentioning
confidence: 81%
“…Using such chimeric molecules expressed in Daudi cells, we previously demonstrated that CD19 Y391 was required for normal function but that Y482 and Y513 were not in this system (8,10). In CD45-transfected plasmacytoma cells, mutation of Y482 and Y513 in cotransfected CD19 reduced the magnitude of the increase in [Ca 2ϩ ] i induced by ligation of the BCR alone (28,29). However, CD19 has six additional cytoplasmic tyrosines of unknown function.…”
Section: D19 Is Expressed On All B Cells Until Late Differentiationmentioning
confidence: 99%
“…(28,29). In this study, we compared the role of all cytoplasmic tyrosines of CD19 in Ca 2ϩ and ERK2 signaling ( Fig.…”
Section: Replicationmentioning
confidence: 99%